2015
DOI: 10.1111/ijfs.13002
|View full text |Cite
|
Sign up to set email alerts
|

Grass carp peptides hydrolysed by the combination of Alcalase and Neutrase: Angiotensin‐I converting enzyme (ACE) inhibitory activity, antioxidant activities and physicochemical profiles

Abstract: In this study, grass carp peptides were prepared by enzymatic hydrolysis of grass carp protein using the combination of Alcalase and Neutrase, and angiotensin-I converting enzyme (ACE) inhibitory activity in vitro, antihypertensive activity in vivo, antioxidant activities, and physicochemical properties of peptides achieved from grass carp protein were characterised after ultrafiltration and desalted processes using mixed ion exchange resins. The purified peptides exhibited strong ACE inhibitory activity (IC 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In an in-vivo experimental setting, after two hours (h) treatment, tested grass carp material showed significant antihypertensive activity (43 mmHg systolic blood pressure (SBP) maximal drop at the dosage of 100 mg kg −1 body weight (BW)) in SHR compared to the control group [42]. Grass carp peptides of size 725–1228 Da, rich in leucine, aspartic acid, phenylalanine and glycine amino acids, at 100 mg kg −1 BW in SHR 6 h post-administration significantly reduced SBP of approximately 30 mm Hg, in comparison to the control group (captopril), the medication of choice, with similar effect at dosage of 10 mg kg −1 BW) and the effect persisted for several weeks after the initial administration [43].…”
Section: Biological Activity Of Fish Fish By-product Protein and mentioning
confidence: 99%
See 3 more Smart Citations
“…In an in-vivo experimental setting, after two hours (h) treatment, tested grass carp material showed significant antihypertensive activity (43 mmHg systolic blood pressure (SBP) maximal drop at the dosage of 100 mg kg −1 body weight (BW)) in SHR compared to the control group [42]. Grass carp peptides of size 725–1228 Da, rich in leucine, aspartic acid, phenylalanine and glycine amino acids, at 100 mg kg −1 BW in SHR 6 h post-administration significantly reduced SBP of approximately 30 mm Hg, in comparison to the control group (captopril), the medication of choice, with similar effect at dosage of 10 mg kg −1 BW) and the effect persisted for several weeks after the initial administration [43].…”
Section: Biological Activity Of Fish Fish By-product Protein and mentioning
confidence: 99%
“…A clear example is that ACE-inhibition activity of jellyfish hydrolysate was enhanced by 8-fold (from IC 50 of 1.28 mg mL −1 to the low end of 0.16 mg mL −1 ) by desalting and gel column chromatographing [33]. Ultra-filtering of grass carp lysate with 10 kDa molecular weight MWCO ultrafiltration (UF) membrane improved IC 50 by about 3-fold (from 0.692 mg mL −1 to 0.272 mg mL −1 ) and further desalting by about 7-fold (from 0.692 mg mL −1 to 0.105 mg mL −1 ) [42]. Even so, precipitating and desalting, frequently applied to plant- and marine-based hydrolysates, is not so common for fish-hydrolysates [24,33,42].…”
Section: Impact Of Enzymatic Digestion and Purification Processes mentioning
confidence: 99%
See 2 more Smart Citations
“…Grass carp (Ctenopharyngodon idella) is one of the 'four major cultured fish species' in China, and it has an annual production that exceeded 5.6 9 10 6 t in 2015, but it has not been developed into a high-value product. Some reports have shown that protein hydrolysates from grass carp prepared using papain, alcalase and neutrase showed antioxidant activity (Li et al, 2012;Chen et al, 2016). However, when preparing hydrolysate from fish sources, one critical problem is the existence of unstable lipid substrates and pro-oxidants (Kristinsson & Rasco, 2000).…”
Section: Introductionmentioning
confidence: 99%